Ethanolic extract of black grapes (Vitis Vinifera) ameliorates overtraining-induced pancreatic β-cells and muscle damage - Ferbian Milas Siswanto; Risha Catra Pradhany; Boedi Prihatini Yenniastoeti; Alex Pangkahila (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2020)
Overtraining is a high-volume, high-intensity, long-duration, and high-frequency training. The heavier physical training, the more oxygen needed for metabolism. Increasing oxygen usage causes an elevation of electron leakage in mitochondria;thus,produce a higher amount of reactive oxygen species (ROS). Antioxidant inhibits oxidative damage in a target molecule. Grapes contain a lot of antioxidants, such as polyphenols and anthocyanins. The purpose of this study was to examine the effect of ethanol extract of Balinese grapes (Vitis vinifera) on β-cells and muscle damage in overtraining-induced rats. This study was a completely randomized experimental study using a posttest only control group design. Samples were 36 male albino rats (Rattus norvergicus), aged 2.5-3 months, divided randomly into two groups. The control group (P0), 18 rats, were given overtraining and placebo of 2 ml distilled water; the treatment group (P1) 18 rats, were given overtraining and 25g/kg.BW ethanol extract of Balinese grapes. The result showed the average amount of pancreatic β-cells in the P0 group was higher than the P1 group (p< 0.001). In addition, the average level of creatine kinase was also higher in the P1 group than those of the P0 group (p<0,001). It can be concluded that the administration of ethanolic extract of Balinese grapes mitigates the damage on pancreatic β-cells and muscle cells induced with overtraining.